The global burden of epilepsy - Sander, Ley (Henry Stewart Talks, 2011)
The global burden of epilepsy, Demographic and epidemiological aspects of Epilepsy around the world, Outcome of epilepsy in resource-poor settings, Aetiology and risk factors for epilepsy, Epilepsy as a stigmatized condition, Health seeking strategies and delivery of epilepsy care in resource-poor countries